Condições bacteriológicas da superfície das poltronas hematológicas par hemodiálise - Ferreira, Natália Cristina [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Health facilities and inanimate surfaces surrounding the patient keep close relation with infections related to care and health, with important centers of contact and transmission of pathogens and can be transferred to many different surfaces through direct and indirect contact. There are numerous studies that show that the hospital items can become vehicles of dissemination, compromising patient safety. Faced with this problem, this study aimed to analyze the bacteriological conditions in the surface of hematologic arm for hemodialysis. After approval by the Research Ethics Committee of the randomization arm, double- blind trial was performed and started sampling the four chair the seven procedures in five different locations in the chair. The product used for routine cleaning of the unit was 70% alcohol with hospital pad composed of 100% cotton in size 30 x 30cm, moistened with 40 ml of 70% ethanol. Bacteriological sampling was used to ensure fenestrated sterile field in the same site collection using Swab. The swab was transported to the laboratory in culture medium gel Stuart for identification. After testing, was performed antibiogram of isolates and sensitivity test in vitro using Kirby and Bauer method with modifications as described by Cooke (1988). For in vitro test used three disinfectants front seats of the isolated bacteria that are considered of great importance in the control of hospital infection. The result demonstrated that the largest colony-forming unit was compared to Staphylococcus sp, followed by Gram-positive bacillus, Staphylococcus aureus, Pseudomonas, Enterobacter cloacae, and Acinetobacter, predominantly Staphylococcus sp on all surfaces of the chair, with predominance in the left arm armchair coinciding with the arm of the patient who has an arteriovenous fistula (70%). Regarding sensitivity, Acinetobacter were sensitive to all antibiotics tested, whereas Pseudomonas were sensitive to sulfa / trimethoprim, ...

Os estabelecimentos de saúde e as superfícies inanimadas que cercam o paciente guardam íntima relação com as infecções relacionadas a assistência e a saúde, sendo importantes focos de contato e de transmissão de agentes patogênicos e podem ser transferidos para as mais diversas superfícies através do contato direto e indireto. Existem inúmeras pesquisas que retratam que os artigos hospitalares podem se tornar veículos de disseminação, comprometendo a segurança do paciente. Diante desta problemática, este estudo objetivou-se em analisar as condições bacteriológicas de superficie de poltronas hematológicas para hemodiálise. Após aprovação do Comitê de Ética em pesquisa foi realizada a randomização das poltronas, duplo cego e iniciou a amostragem das quatro cadeira nos sete procedimentos em cinco locais diferentes na poltrona. O produto utilizado para higienização de rotina na unidade foi o álcool a 70% com compressa hospitalar composta de tecido 100% algodão em dimensão de 30 x 30 cm, umedecida com 40 ml de álcool 70%. Para amostragem bacteriológica utilizou-se campo estéril fenestrado para garantir coleta sempre no mesmo local utilizando Swab. O Swab foi transportado para o laboratório em meio de cultura gel Stuart para identificação. Após foi realizado teste de antibiograma das bactérias isoladas e teste de sensibilidade “in vitro” utilizando método de Kirby e Bauer com modificações conforme descrito por Corrêa (1988). Para o teste “in vitro” utilizou-se três desinfetantes frente as bactérias isoladas das poltronas que são consideradas de grande importância no controle de infecção hospitalar. O resultado demostrou que a maior unidade formadora de colônia foi em relação ao Staphilococcus sp, seguido de bacilus Gram positivo, Staphilococcus aureus, Pseudomonas, Enterobacter cloacae e Acinetobacter, com predominância do Staphilococcus sp em todas as ...
Keywords: Hematologia; Bacteriologia; Hemodialise; Infeccão hospitalar; Bacteriology